Effect of Lemon Marination on Polycyclic Aromatic Hydrocarbons (PAH) and Quality of Chicken Satay - Citra Nurma Yunita; Lilik Eka Radiati; Djalal Rosyidi (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of different lemon marinates on Polycyclic Aromatic Hydrocarbons (PAHs) and quality of chicken satay. The percentages of lemon used 0%, 5 %, 10 % and 15 %. Chicken meat was marinated for 10 minutes in a homogeneous. The study used a Nested Completely Randomized Design. Parameters used were physical quality (pH, cooking loss and WHC), chemical quality (moisture, fat and protein content) and Polycyclic Aromatic Hydrocarbons (PAHs). Data were analyzed using Analysis of Variance (ANOVA), if the results of statistical analysis significant or very significant differences were obtained Duncan's test (UJBD) and descriptive PAH. The results of statistical analysis showed that the use of lemons marinates with different proportions had a very significant effect (P<0,01) on pH, cooking loss, WHC and moisture, fat content had a significant effect (P<0,05) but had no significant effect (P>0,05) on protein content. Chicken satay with 15% lemon marinates showed non-detectable results PAH.Â The study concluded that lemon marinates can reduce the content of PAH carcinogens and affect the quality of chicken satay. The lowest levels of PAHs were found in the chicken satay that was marinated with a 15% lemon marinates.